A Case of Pyogenic Vertebral Osteomyelitis: Importance of Physical Examination for Correct Diagnosis. (18th June 2016) - Ozaka, Akihiro; Onishi, Tsubasa; Ueda, Yuki; Kenzaka, Tsuneaki; Matsumura, Masami
Abstract : A 76‐year‐old‐man was admitted to hospital because of fever and back pain. Blood cultures yielded extended‐spectrum beta‐lactamase‐producing Escherichia coli (ESBLEC). We suspected pyogenic vertebral osteomyelitis (PVO) secondary to urosepsis. However, magnetic resonance imaging (MRI) of the lumbar spine did not reveal findings of PVO. The extent of tenderness in the back converged on the lumbar spine on repeated physical examinations. We decided to perform a second MRI, and it showed hypointensity on T1‐weighted images and contrast enhancement in L3/L4. Culture of computed tomography guided L3/L4 disc biopsy yielded ESBLEC. Daily repeated physical examinations contributed to the correct diagnosis.